Pengaruh Pekerjaan dan Perhatian Orang Tua Terhadap Kedisiplinan Siswa Kelas Atas di SD Muhammadiyah 15 Sumber Surakarta Tahun 2015/2016 - Nurhayati, Umi; , Minsih, S. Ag. M. Pd (2016)
This study aims to determine the effect of: (1) the job of parents to discipline students of high grade SD Muhammadiyah 15 Sumber Surakarta (2) the attention of parents to discipline students of high grade SD Muhammadiyah 15 Sumber Surakarta (3) work and attention of parents to discipline students high grade SD Muhammadiyah 15 Sumber Surakarta. The study included ex-posfacto type of research. The study population was all students upscale SD Muhammadiyah 15 Sumber Surakarta who numbered about 50, the study sample included 30 students. The technique of collecting data using questionnaires, documentation, and interviews. Data were analyzed using multiple regresilinier, t test, F test, the coefficient of determination, the relative contribution, the effective contribution that preceded the prerequisite test is a test of normality and linearity test. Based on the analysis concluded: (1) The work of parents has no effect on student discipline. Based on t test results: -t_table≤t_count X_1≤t_table is -2,052≤1,827≤2,052. (2) Attention parents has no effect on student discipline. Based on t test results: -: -t_table≤t_count X_2≤t_table is -2,052≤1,513≤2,052. (3) work and attention of parents has no effect on student discipline. Based on the test results F: F_count>F_table is 3,500 ˃ 3,35 and a significance probability value ˃0,05 is 0,44. It can be concluded that the work and the attention of parents has no effect on student discipline of high grade SD Muhammadiyah Surakarta Sumber 15 tahun 2015/2016. Keywords: job of parents, parents attention, discipline students.